Feeding hungry ghosts: grief, gender, and protest in Hong Kong. Issue 3 (3rd July 2022) - Cheng, Sealing
ABSTRACT: Following a particularly violent police operation inside the Prince Edward subway station on August 31 2019, during the anti-extradition movement in Hong Kong, a group of older women performed mourning rituals for the possibly dead outside the subway exit for almost one hundred days. In view of increasing police surveillance, violence, and arrests, these women's religious practices and the sociality they generated constituted a form of infrapolitics. By carefully performing their gendered roles as funerary experts, these women created a makeshift shrine that operated symbolically as a public sphere of dissent. This paper examines the making of their shrine in the context of widespread public discontent about police brutality, and by extension, state violence in a broader political-economic context. Without knowing who was being memorialized, the continuous flow of mourners to the Prince Edward Station shrine compels scholars to consider what these possible deaths could mean and what other losses they were accounting for. Through the lens of infrapolitics, these women's creative appropriation of mourning rituals directs our attention to the amebic vitality of resistance and its persistence against great odds.